Equilibrium Selection with Risk Dominance in a Multiple-unit Unit Price Auction - Anette Boom (Copenhagen Business School (CBS), Department of Economics, 2008)
This paper uses an adapted version of the linear tracing procedure, suggested by Harsanyi and Selten (1988), in order to discriminate between two types of multiple Nash equilibria. Equilibria of the same type are pay-off equivalent in the analysed multiple-unit unit price auction where two sellers compete in order to serve a fixed demand. The equilibria where the firm with the larger capacity bids the maximum price, serves the residual demand and is undercut by the low capacity firm that sells its total capacity risk dominate the equilibria where the roles are interchanged.
hdl:10398/7664
Keywords: G10; 330